Hyperhemolysis in a patient with sickle cell disease and recent SARS‐CoV‐2 infection, with complex auto‐ and alloantibody work‐up, successfully treated with tocilizumab. Issue 7 (30th May 2022) - Fuja, Christine; Kothary, Vishesh; Carll, Timothy Clifford; Singh, Savita; Mansfield, Paul; Wool, Geoffrey D.
Abstract: Background: Hyperhemolysis syndrome (HHS) is a severe delayed hemolytic transfusion reaction seen in sickle cell disease (SCD) patients, characterized by destruction of donor and recipient RBCs. It results in a drop in hemoglobin to below pretransfusion levels and frequently reticulocytopenia. Case Report: We report a case of a man in his thirties with SCD with a recent hospitalization 2 weeks prior for COVID‐19. His red cell antibody history included anti‐Fy(a) and warm autoantibody. At that time, he was given 2 units of RBC and discharged with a hemoglobin of 10.2 g/dl. He returned to the hospital approximately 1.5 weeks later with hemoglobin 6.0 g/dl and symptoms concerning for acute chest syndrome. Pretransfusion testing now showed 4+ pan‐agglutinin in both gel‐based and tube‐based testing. Alloadsorption identified an anti‐N and a strong cold agglutinin. Three least incompatible units were transfused to this patient over several days, with evidence of hemolysis. Further reference lab work revealed anti‐Fy a, anti‐Fy b, anti‐Le a, anti‐Le b, and an anti‐KN system antibody. The patient's hemoglobin nadired at 4.4 g/dl. The patient was treated with a single dose of tocilizumab, his hemoglobin stabilized, and he was discharged. Discussion: We present a case of HHS proximate to recent SARS‐CoV‐2 infection with multiple allo and autoantibodies identified. Information on the relationship between SARS‐CoV‐2 infection and HHS is limited; however, it is possible that inflammation related to COVID‐19 could predispose to HHS. Tocilizumab is an approved treatment for COVID‐19. Additionally, tocilizumab appears to be a promising treatment option for patients with HHS.